2019
DOI: 10.1007/s41669-019-00181-y
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Survival of Patients Treated with Adjuvant Nivolumab Who Have Melanoma with Lymph Node Involvement or Metastatic Disease After Complete Resection

Abstract: Introduction Nivolumab demonstrated significant recurrence-free survival (RFS) gains versus ipilimumab in the Check-Mate-238 trial, whereas the CA184-029 trial showed superior RFS gains for ipilimumab versus placebo. No head-to-head trial data were available to compare the efficacy of nivolumab to that of observation, so indirect treatment comparisons were required. Additionally, overall survival (OS) data were not available from CheckMate-238, and the clinical pathway for melanoma has changed significantly ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Nevertheless, other approaches may also be helpful to consider within the context of informing HTA. For example, Batteson et al 27 considered a range of approaches to both directly and indirectly estimate OS for patients with melanoma treated with adjuvant nivolumab. Repeating the analyses described in our study and those conducted by others for different patient populations would further increase the understanding of the most appropriate methods to produce suitable survival estimates for HTA.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, other approaches may also be helpful to consider within the context of informing HTA. For example, Batteson et al 27 considered a range of approaches to both directly and indirectly estimate OS for patients with melanoma treated with adjuvant nivolumab. Repeating the analyses described in our study and those conducted by others for different patient populations would further increase the understanding of the most appropriate methods to produce suitable survival estimates for HTA.…”
Section: Discussionmentioning
confidence: 99%
“…For nivolumab, due to immature data, no survival curves for overall survival were not available until late 2020. Different approaches to construct surrogates for the missing survival curve were presented [71,72], which usually project results from study CA184-029 (ipilimumab vs. placebo) [21] to the relationship ipilimumab vs. nivolumab, which was investigated in study Checkmate-238 [33]. Batteson et.al [71].…”
Section: Discussionmentioning
confidence: 99%
“…Different approaches to construct surrogates for the missing survival curve were presented [71,72], which usually project results from study CA184-029 (ipilimumab vs. placebo) [21] to the relationship ipilimumab vs. nivolumab, which was investigated in study Checkmate-238 [33]. Batteson et.al [71]. presented an alternative surrogate based on systematic research of available literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CheckMate 238 obtained lower HR (0.73; 95% CI 0.55–0.95); however, it was developed with two treatment arms (nivolumab and ipilimumab) without an observation arm as in the previous study. A recent paper analyzed the potential values of HR in CheckMate 238, considering whether this study would have been conducted with a comparator observation: it showed that nivolumab would have a significant RFS benefit over observation, with an HR value of 0.54 (95% CI 0.41–0.69), similar to those of COMBI-AD and KEYNOTE-054 [ 57 ].…”
Section: Discussionmentioning
confidence: 99%